FACTOR MODEL FOR ASSESSING THE ROLE OF SMALL AND MEDIUM-SIZED BUSINESS IN THE UKRAINIAN AGRICULTURAL INDUSTRY COMPLEX - Chub, Anton (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article proves that the main problem in the development of small business in the agro-industrial complex of Ukraine is limited opportunities for attracting capital investments and, as a result, a decrease in labor productivity due to low capital-labor ratio. Under such conditions, the growing role of small business at the expense of large enterprises leads to a drop in real production volumes. Today, theoretical studies of small and medium enterprises development in the domestic practice of doing business are both legal and scientific. According to the legislation of Ukraine, the state undertakes: to create favorable conditions and ensure the development of small and medium enterprises, to stimulate their investment activities, to promote goods and services on the market. Among the instruments of regulatory policy: deregulation in the field of taxation, financial support through government lending and guarantee programs, comprehensive infrastructure development, simplification of licensing procedures, guaranteeing rights through the judiciary, assistance in using new technologies, attracting small and medium enterprises, state needs, etc. It was found that among the main problems that hinder the entrepreneurship development are: imperfection of the legislative framework; high tax pressure; lack of real state support for small business, including financial, credit and investment support, and the like. Enterprises of the agro-industrial complex in the course of their economic activities face the same problems as others. The scientific originality of this work is the improvement of the methodology for assessing the role of small and medium-sized businesses in the agro-industrial complex of Ukraine development on the basis of deterministic factor models of economic analysis, in contrast to the existing ones, it allows to eliminate the influence of inflationary processes and performs a quantitative assessment of structural changes in the use of labor and their labor productivity.